2014
DOI: 10.1194/jlr.m050864
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Nceh1 augments 25-hydroxycholesterol-induced ER stress and apoptosis in macrophages

Abstract: Atherosclerotic cardiovascular diseases are the leading cause of mortality in industrialized countries, despite advances in the management of coronary risk factors. Heart attacks arise from the thrombotic occlusion of coronary arteries following the rupture of plaques. Characteristic of these rupture-prone plaques is their lipid-rich nature due to the presence of cholesteryl ester (CE)-laden macrophage foam cells ( 1 ).The hydrolysis of intracellular CE, the initial step of reverse cholesterol transport, is ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 60 publications
1
33
0
1
Order By: Relevance
“…Because of the effects of the schweinfurthin compounds on FPP and GGPP and our earlier observation that they induce a form of ER stress [22], our hypothesis was that the schweinfurthins could more globally alter isoprenoid pathway metabolites and cholesterol homeostasis in a manner reminiscent of oxysterol 25-hydroxycholesterol [23]. Herein, we describe the effects of 3dSB on cholesterol content and cholesterol synthesis in cell lines with varying sensitivity to the antiproliferative effects of the schweinfurthins.…”
Section: Introductionmentioning
confidence: 95%
“…Because of the effects of the schweinfurthin compounds on FPP and GGPP and our earlier observation that they induce a form of ER stress [22], our hypothesis was that the schweinfurthins could more globally alter isoprenoid pathway metabolites and cholesterol homeostasis in a manner reminiscent of oxysterol 25-hydroxycholesterol [23]. Herein, we describe the effects of 3dSB on cholesterol content and cholesterol synthesis in cell lines with varying sensitivity to the antiproliferative effects of the schweinfurthins.…”
Section: Introductionmentioning
confidence: 95%
“…ERS-induced apoptosis in macrophages may be due to neutral cholesterol ester hydrolase 1 (Nceh1). Sekiya et al [86] reported that Nceh1-deficient thioglycollate-elicited peritoneal macrophages (TGEMs) were susceptible to apoptosis induced by oxysterols, particularly 25-hydroxycholesterol (25-HC). Incubation with 25-HC caused massive accumulation of 25-HC ester in the ER due to its defective hydrolysis function, thereby activating ERS signaling proteins such as CHOP.…”
Section: Endoplasmic Reticulum Stress Regulates Cardiovascular Physiomentioning
confidence: 99%
“…It has been shown that cytotoxic oxysterols induced apoptosis via enhancing ER stress . 7ÎČ‐Hydroxycholesterol activated IRE1α by phosphorylation, an ER transmembrane sensor that activates the UPR to maintain the ER and cellular function.…”
Section: Resultsmentioning
confidence: 99%